PROGRAM PENGELOLAAN SAMPAH BERBASIS MASYARAKAT DI KANAL BANJIR BARAT (KBB) KOTA SEMARANG - Reny Yesiana; Wiwandari Handayani; Mega Anggraini; Bintang Septiarani (Jurnal Riptek, 2020)
Flood management is one of the development priorities in Semarang City because itcauses huge losses and damage to assets and lives. The flood incident in Kaligarangthat occurred in 1990 was the driving force penetrate the anticipating meassure forthe risk of flooding in the West Flood Canal. The Semarang City Government hasmade efforts to minimize the risk of flooding through the construction of theJatibarang DAM. Not only that, grassroot approaches are also being developed as aneffort to reduce the impact of flooding in the city of Semarang. As a form of supportfor the Semarang City government, Mercy Corps Indonesia (MCI) collaborates with theInitiative for Urban Climate Change and Environment (IUCCE) and the Initiative forRegional Development and Environmental Management (IRDEM) with financialsupport from the Z Zurich Foundation seeks to help communities in the West FloodCanal, Semarang in managing their waste with a community-based wastemanagement system in five sub-districts (kelurahan). The purpose of this article is toexamine a community-based waste management program and its benefits for thecommunity in five kelurahan located in the West Flood Canal of Semarang City so thatit can be a lesson for other areas. The method used in this study is a qualitativemethod, with primary data collection techniques semi-open interviews. The samplingtechnique used for this interview was purposive sampling because the informants wereselected according to their competence. In addition, observations were made on eachactivity and document review. From this study, it is known that the people in fivekelurahan in the West Flood Canal have become more empowered in managing theirwaste through this program. The community empowerment process in this programcan be both a lesson and a challenge for community-based waste management inSemarang City.